2014
DOI: 10.1016/j.rse.2013.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring conterminous United States (CONUS) land cover change with Web-Enabled Landsat Data (WELD)

Abstract: Egorov, A.; Potapov, P V.; Stehman, S V.; Tyukavina, A; Turubanova, S A.; Roy, D. P.; Goetz, S J.; Loveland, T R.; Ju, J; Kommareddy, A.; Kovalskyy, V.; Forsyth, C; and Bents, T, "Monitoring conterminous United States (CONUS) land cover change with Web-Enabled Landsat Data (WELD)" (2014 Forest cover loss and bare ground gain from 2006 to 2010 for the conterminous United States (CONUS) were quantified at a 30 m spatial resolution using Web-Enabled Landsat Data available from the USGS Center for Earth Resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(102 citation statements)
references
References 59 publications
0
98
1
3
Order By: Relevance
“…At the Landsat resolution, global VCF tree cover products have been generated for 2000 and 2005 [48]. Recent advances in remote sensing demonstrated that Landsat images could be used to create near cloud-free composites by exhaustively mining the Landsat archive [20,74], and the annually composited Landsat images could also be used to characterize land cover and change [20,75]. This may create an opportunity to produce continuous fields of land cover at annual time steps using Landsat data.…”
Section: Discussionmentioning
confidence: 99%
“…At the Landsat resolution, global VCF tree cover products have been generated for 2000 and 2005 [48]. Recent advances in remote sensing demonstrated that Landsat images could be used to create near cloud-free composites by exhaustively mining the Landsat archive [20,74], and the annually composited Landsat images could also be used to characterize land cover and change [20,75]. This may create an opportunity to produce continuous fields of land cover at annual time steps using Landsat data.…”
Section: Discussionmentioning
confidence: 99%
“…Landsat images have been widely used in land cover classification because of their stable imaging quality [1,31,32,[58][59][60]. In this study, Level 1 terrain-corrected (L1T) Landsat images were selected as the primary data source for the land cover classifications.…”
Section: Data and Pre-processingmentioning
confidence: 99%
“…Compositing procedures are applied independently on a per-pixel basis to the gridded WELD time series to reduce cloud and aerosol contamination, fill missing values due to the SLC failure (that removed about 22% of each Landsat ETM+ image [56]), and to reduce data volume. The WELD data have an established land cover mapping provenance and have been used, for example, to make land cover, land cover change, burned area, and field size maps at national scale [24,[57][58][59].…”
Section: Existing Land Cover Maps For 2008 and 2011mentioning
confidence: 99%
“…Multi-date composites are not suitable as input to the basic IRMAD algorithm, since only a single linear transformation is calculated per composite pair, which would not accommodate all the potential date combinations present in the composites. Although several forest monitoring systems perform change detection based on annual rank-based metrics [28,58] and it would have simplified the LALCUM system, we expected that the multiple forms of land cover change which need to be detected in our study area would require a more sensitive spectral change detection method. Since almost 22% of each of the bi-temporal Landsat ETM+ image is lost due to the SLC-off error, change detection could only be effectively applied across about 66% of the study area.…”
Section: To 2011 Change Detection and Validationmentioning
confidence: 99%